Identitas dan Orientasi Nilai Kultural Mahasiswa Calon Guru - Akhmad, Sudaryat Nurdin (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
The research aims to learn profile of identity status and cultural value orientation of teacher prospective student. The research method that used is descriptive by qualitative approach. The research sample involves 80 students of education program at Universitas Pendidikan Indonesia that are chosen by using technique of multi stage cluster sampling. The collected data by questionnaire is analysized statisticaly. The research result shows that majority of teacher prospective students is on low cultural identity status. They are forecloser and diffusion. They who are in achievement status and moratorium, that is accused as high identity status, each of them is belonged by least of forth of students quantity. Four values that become strongest preferences for students are economic value, science value, social value and religious value. Some students that have achievement cultural identity status belong strong orientation on science value, then religious value and social value and economic value. Moratorium status put stronger orientation on economic value, social, aesthetic, and religious and the last is science. Foreclosure status put more orientation on economic value, social, and power. Besides, diffusion status put more orientation on economic value, power, social, aesthetic and religious.